Performance of Ecological Pervious Concrete Prepared with Sandstone/Limestone-Mixed Aggregates - Lei Wang; Zhikui Liu; Yan Yan; Bingyan Huang; Yongxiong Xie (Geofluids)
To understand the performance of ecological pervious concrete prepared with mixed sandstone/limestone aggregates, limestone and sandstone were used as two aggregates. The sandstone-to-limestone volume ratio was calculated in 0 : 1, 0.25 : 0.75, 0.5 : 0.5, 0.75 : 0.25, and 1 : 0 in coarse aggregate to prepare ecological pervious concrete specimens. The compressive test, water permeability test, cooling test, evaporation test, alkaline test, and scanning electron microscope (SEM) tests were carried out with qualified compressive strength as the indicator to determine the optimum sandstone-to-limestone volume ratio for the ecological pervious concrete. The results show that the water permeability, cooling property, and evaporation property of the ecological pervious concrete increase with the sandstone content. When the sandstone-to-limestone volume ratio is less than 0.32 : 0.68 (the substitution rate of sandstone for limestone in ecological pervious concrete is 32%), the strength of ecological pervious concrete meets the requirements of 5 MPa and achieves the best permeability coefficient of 9 mm/s. This realizes the full use of net water storage and cooling capacity of the ecological pervious concrete and makes the ecological pervious concrete meet the construction requirement of slope protection in sponge cities in the south.